THE INFLUENCE OF MARKETING STRATEGIES ON INCREASING YADEL LAUNDRY SERVICE PRODUCTS - indah permata sari; Cece, S.E., M.Si (SEAN Institute, 2023)
This research seeks to explore how marketing strategies impact the enhancement of Yadel Laundry's service offerings. The study employs a quantitative research approach with a cross-sectional design. Data was collected by distributing questionnaires to 150 Yadel Laundry customers in the Batang Kuis District. The collected data was then analyzed using multiple linear regression methods facilitated by statistical software. The findings indicate that the marketing mix, which comprises elements such as product, pricing, promotion, and distribution, exerts a significant influence on the improvement of Yadel Laundry's service products. Furthermore, customer satisfaction is identified as a mediating factor between these marketing strategies and the enhancement of Yadel Laundry's service products, suggesting that higher customer satisfaction, resulting from an effective marketing mix, has a more substantial impact on the improvement of Yadel Laundry's service products. This research contributes significantly to Yadel Laundry's management by providing insights into effective marketing strategies for enhancing their service products. The managerial implication of this study underscores the importance of giving more attention to managing the marketing mix and customer satisfaction as vital factors in improving Yadel Laundry's service offerings.